Penyuluhan Kesehatan Gigi dan Mulut dalam rangka Menurunkan Indeks Plak pada murid SDN 1 Ajun Jeumpet Darul Imarah Kabupaten Aceh Besar - Reca, Reca; Salfiyadi, Teuku; Cut Aja Nuraskin; Srirahayu, Eka; Nurhaida (Poltekkes Kemenkes Aceh, 2023)
Dental plaque is the most potential factor for dental disease. This community service aimsto conduct dental health counseling in reducing plaque index in SDN 1 students adjunct jeumpet kec. Darul Imarah Aceh Besar Regency. This community service is descriptive method, with the target being Class I and I1 students at SDN Ajun Jeumpet Aceh Besar Regency totaling 30 people. Data analysis using univariate analysis. The intervention provided was in the form of counseling, plaque index examination, and toothbrush. The results showed a decrease in plaque index before and after intervention (counseling) namely before intervention (counseling) (100%) with bad category namely (2.1-3.0), to (70%) plaque index with good category ie (0-1) after intervention (counseling). It can be concluded that there was a decrease in plaque index after counseling. It is recommended to the school that there is regular counseling to students about the importance of maintaining oral and dental health.